Evaluation of System Modelling Techniques for Waste Identification in Lean Healthcare Applications - Alkaabi M; Simsekler MCE; Jayaraman R; Al Kaf A; Ghalib H; Quraini D; Ellahham S; Tuzcu EM; Demirli K (Dove Medical Press, 2021)
Maitha Alkaabi,1 Mecit Can Emre Simsekler,1 Raja Jayaraman,1 Abdulqader Al Kaf,1 Hussam Ghalib,2 Dima Quraini,2 Samer Ellahham,2 E Murat Tuzcu,2 Kudret Demirli3 1Department of Industrial and Systems Engineering, Khalifa University of Science and Technology, Abu Dhabi, United Arab Emirates; 2Heart and Vascular Institute, Cleveland Clinic Abu Dhabi, Abu Dhabi, United Arab Emirates; 3Department of Mechanical, Industrial and Aerospace Engineering, Concordia University, Montreal, CanadaCorrespondence: Mecit Can Emre SimseklerDepartment of Industrial and Systems Engineering, Khalifa University of Science and Technology, P.O. Box 127788, Abu Dhabi, United Arab EmiratesTel +9712 501 8410Fax +971 2 447 2442Email emre.simsekler@ku.ac.aePurpose: Waste identification plays a vital role in lean healthcare applications. While the value stream map (VSM) is among the most commonly used tools for waste identification, it may be limited to visualize the behaviour of dynamic and complex healthcare systems. To address this limitation, system modelling techniques (SMTs) can be used to provide a comprehensive picture of various system-wide wastes. However, there is a lack of evidence in the current literature about the potential contribution of SMTs for waste identification in healthcare processes.Methods: This study evaluates the usability and utility of six types of SMTs along with the VSM. For the evaluation, interview-based questionnaires were conducted with twelve stakeholders from the outpatient clinic at the Heart and Vascular Institute at Cleveland Clinic Abu Dhabi.Results: VSM was found to be the most useful diagram in waste identification in general. However, some SMTs that represent the system behaviour outperformed the VSM in identifying particular waste types, e.g., communication diagram in identifying over-processing waste and flow diagram in identifying transportation waste.Conclusion: As behavioural SMTs and VSM have unique strengths in identifying particular waste types, the use of multiple diagrams is recommended for a comprehensive waste identification in lean. However, limited resources and time, as well as limited experience of stakeholders with SMTs, may still present obstacles for their potential contribution in lean healthcare applications.Keywords: lean healthcare, value stream map, system modelling techniques, waste identification, kaizen, system approaches, healthcare operations